A New University Model proposed by the International Telematic University UNINETTUNO: Teaching and Learning on the Internet - Maria Amata Garito (Modern Perspectives in Language, Literature and Education Vol. 5, 2021)
The globalisation process and the development of the knowledge society were sparked by the convergence of telecommunications and computer science, the implementation of computer-based networks, and the integration of languages, which overcame space and time constraints. We are witnessing a true revolution based on knowledge multiplication and its associated applications, as well as knowledge codification, memorization, and transfer. The challenges that educational institutions, and the University in particular, face are linked to the fact that classrooms or lecture halls are no longer the only places where one can follow study courses: anyone from anywhere, if he has the necessary technological equipment and materials, can create his own environment in which to continue his own educational and self-learning activities. This is why, through study, we must identify new university models and psycho-pedagogic theories that will allow for the development of new Internet-based teaching and learning models. This paper explains the university model proposed by the International Telematic University UNINETTUNO, which has quickly gained international recognition.